2017
DOI: 10.17221/96/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant coagulase-negative staphylococci in healthy dogs

Abstract: ABSTRACT:The objective of this study was to evaluate the prevalence of coagulase-negative staphylococci in healthy dogs and to determine whether methicillin-resistant staphylococci expressed the mecA gene. Nasal and rectal swab samples were taken from 50 clinically healthy dogs. The prevalence of coagulase-negative staphylococci was evaluated according to phenotypic properties. The agar diffusion method was applied to evaluate antimicrobial resistance and the prevalence of methicillin resistance was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
6
2
Order By: Relevance
“…Among pets, very sparse data are available on the specific nasal MRCoNS rates. Lower rates (1–15%) than those detected here (17%) have been observed among healthy dogs from several body sites (nasal, rectal, oral, anal, belly) (Vengust et al, 2006; Bagcigil et al, 2007; Aslantas et al, 2013; Gandolfi-Decristophoris et al, 2013; Garbacz et al, 2013; Chah et al, 2014; Davis et al, 2014; Wedley et al, 2014; Siugzdaite and Gabinaitiene, 2017). Interestingly, MRCoNS was isolated from 42% of healthy non-vet visiting and non-antimicrobial treated Labrador retrievers in the United Kingdom (Schmidt et al, 2014).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Among pets, very sparse data are available on the specific nasal MRCoNS rates. Lower rates (1–15%) than those detected here (17%) have been observed among healthy dogs from several body sites (nasal, rectal, oral, anal, belly) (Vengust et al, 2006; Bagcigil et al, 2007; Aslantas et al, 2013; Gandolfi-Decristophoris et al, 2013; Garbacz et al, 2013; Chah et al, 2014; Davis et al, 2014; Wedley et al, 2014; Siugzdaite and Gabinaitiene, 2017). Interestingly, MRCoNS was isolated from 42% of healthy non-vet visiting and non-antimicrobial treated Labrador retrievers in the United Kingdom (Schmidt et al, 2014).…”
Section: Discussioncontrasting
confidence: 79%
“…Interestingly, Tetracycline was only detected among human strains, while this antibiotic is widely used in both human and animal medicine (Guardabassi et al, 2004). The lack of resistance among animal strains differs from former studies among both healthy and clinical canine isolates, with rates ranging between 40 and 81% (Aslantas et al, 2013; Kern and Perreten, 2013; Chah et al, 2014; Wedley et al, 2014; Couto et al, 2016; Siugzdaite and Gabinaitiene, 2017). Such differences are most likely due to the groups studied and the geographical area of the sampling.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Similar to previous studies [ 22 , 26 , 27 ], S . aureus had the highest levels of AMR and MDR followed by the CoNS [ 1 , 45 , 46 ]. Unfortunately, in this study, CoNS were not identified to species level nor was testing for mecA gene done since it was not part of the diagnostic protocol used by the laboratory that provided the study data.…”
Section: Discussionmentioning
confidence: 99%